1993
DOI: 10.1002/aja.1001980303
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expression of pregnancy‐specific glycoprotein gene rnCGM1 in rat placenta

Abstract: As a basis towards a better understanding of the role of the pregnancy-specific glycoprotein (PSG) family in the maintenance of pregnancy, detailed investigations are described on the expression of a recently identified rat PSG gene (rnCGMl) at the mRNA and protein levels. Using specific oligonucleotide primers, rnCGMl transcripts were identified after reverse transcription, polymerase chain reaction, and hybridization with a radiolabelled, internal oligonucleotide. Transcripts were only found in significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…On the other hand, simi- At present, the function of CealO is completely obscure. This is also true for the PSGs, which also represent secreted members of the CEA family, although roles in trophoblast invasion or specific suppression of the maternal immune system during pregnancy have been discussed for PSGs [52]. CealO lacks, however, the ArgGlyAsp-related amino acid sequence motif, presumed to be functionally important, which is present in most human and murine PSGs and is known to be involved in interaction of certain extracellular matrix proteins with their cellular integrin receptors [55].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, simi- At present, the function of CealO is completely obscure. This is also true for the PSGs, which also represent secreted members of the CEA family, although roles in trophoblast invasion or specific suppression of the maternal immune system during pregnancy have been discussed for PSGs [52]. CealO lacks, however, the ArgGlyAsp-related amino acid sequence motif, presumed to be functionally important, which is present in most human and murine PSGs and is known to be involved in interaction of certain extracellular matrix proteins with their cellular integrin receptors [55].…”
Section: Discussionmentioning
confidence: 99%
“…They are synthesised in the syncytiotrophoblast of the human placenta and in the giant cells and spongiotrophoblast of the rodent placenta (Lei et al 1992, Rebstock et al 1993, Kromer et al 1996, Zhou et al 1997. The PSG family belongs to the carcinoembryonic antigen (CEA) family, which also includes the CEA-related adhesion molecules (CEACAMs), and is part of the immunoglobulin (Ig) superfamily (Brummendorf & Rathjen 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-anchored CEACAMs are widely expressed during embryonic development and in adult tissues, and are implicated in multiple aspects of cell signalling, tissue homeostasis and disease, including carcinogenesis and regulation of immune and metabolic functions (Han et al 2001, Zebhauser et al 2005. PSGs and some CEACAMs are expressed almost exclusively in trophoblasts of the haemochorial placenta of rodents and primates, suggesting potential functional convergence between these otherwise divergent gene families (Rebstock et al 1993, Zhou & Hammarstrom 2001.…”
Section: Introductionmentioning
confidence: 99%
“…C-CAM is a member of the CEA gene family, which comprises several structurally related proteins (Thompson et al 1991), and it has previously been demonstrated that rat placenta expresses proteins belonging to the PSG subgroup of the CEA family (Rebstock et al 1993;Ogilvie et al 1989). However, antibodies recognizing rat PSGs gave a completely different spatiotemporal staining pattern, demonstrating that the antibodies against C-CAM did not crossreact with PSG.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pregnancy-specific glycoproteins (PSGs) which, like C-CAM, belong to the CEA gene family, are expressed at high levels in placentae of both humans and rodents (Rebstock et al 1993;Ogilvie et al 1989). Because there can be considerable immunological crossreactivity among different members of the CEA family, it was important to demonstrate that the staining observed with anti-C-CAM antibodies indeed reflected expression of C-CAM and not of PSG.…”
Section: Spatiotemporal Expression Of C-cam In Placentamentioning
confidence: 99%